The impact of genomic variation on protein phosphorylation states and regulatory networks. Issue 5 (16th May 2022) - Grossbach, Jan; Gillet, Ludovic; Clément‐Ziza, Mathieu; Schmalohr, Corinna L; Schubert, Olga T; Schütter, Maximilian; Mawer, Julia S P; Barnes, Christopher A; Bludau, Isabell; Weith, Matthias; Tessarz, Peter; Graef, Martin; et al.
Abstract: Genomic variation impacts on cellular networks by affecting the abundance (e.g., protein levels) and the functional states (e.g., protein phosphorylation) of their components. Previous work has focused on the former, while in this context, the functional states of proteins have largely remained neglected. Here, we generated high‐quality transcriptome, proteome, and phosphoproteome data for a panel of 112 genomically well‐defined yeast strains. Genetic effects on transcripts were generally transmitted to the protein layer, but specific gene groups, such as ribosomal proteins, showed diverging effects on protein levels compared with RNA levels. Phosphorylation states proved crucial to unravel genetic effects on signaling networks. Correspondingly, genetic variants that cause phosphorylation changes were mostly different from those causing abundance changes in the respective proteins. Underscoring their relevance for cell physiology, phosphorylation traits were more strongly correlated with cell physiological traits such as chemical compound resistance or cell morphology, compared with transcript or protein abundance. This study demonstrates how molecular networks mediate the effects of genomic variants to cellular traits and highlights the particular importance of protein phosphorylation. Synopsis: A systematic analysis of how genetic variation in a yeast cross affects the transcriptome, the proteome and the phosphoproteome reveals multi‐layered changes in regulatory networks that ultimately have an impact on hundreds of cellular traits. Genetic effects on transcripts are transmitted to protein abundance changes for most genes. Phosphorylation states are crucial for unraveling genetic effects on signaling networks and cell physiology. Phosphorylation QTLs tend to co‐occur with missense variants. Overall, the study indicates complex post‐transcriptional QTL effects on signaling networks, for example in the mating pheromone pathway. Abstract : A systematic analysis of how genetic variation in a yeast cross affects the transcriptome, the proteome and the phosphoproteome reveals multi‐layered changes in regulatory networks that ultimately have an impact on hundreds of cellular traits.